Acute, next‐generation AMPK activation initiates a disease‐resistant gene expression program in dystrophic skeletal muscle. Issue 5 (5th April 2023) - Ng, Sean Y.; Mikhail, Andrew I.; Mattina, Stephanie R.; Manta, Alexander; Diffey, Ian J.; Ljubicic, Vladimir
Abstract: Duchenne muscular dystrophy (DMD) is a life‐limiting neuromuscular disorder characterized by muscle weakness and wasting. Previous proof‐of‐concept studies demonstrate that the dystrophic phenotype can be mitigated with the pharmacological stimulation of AMP‐activated protein kinase (AMPK). However, first‐generation AMPK activators have failed to translate from bench to bedside due to either their lack of potency or toxic, off‐target effects. The identification of safe and efficacious molecules that stimulate AMPK in dystrophic muscle is of particular importance as it may broaden the therapeutic landscape for DMD patients regardless of their specific dystrophin mutation. Here, we demonstrate that a single dose of the next generation, orally‐bioactive AMPK agonist MK‐8722 (MK) to mdx mice evoked skeletal muscle AMPK and extensive downstream stimulation within 12 h post‐treatment. Specifically, MK elicited a gene expression profile indicative of a more disease‐resistant slow, oxidative phenotype including increased peroxisome proliferator‐activated receptor ɣ coactivator‐1⍺ activity and utrophin levels. In addition, we observed augmented autophagy signaling downstream of AMPK, as well as elevations in critical autophagic genes such as Map1lc3 and Sqstm1 subsequent to the myonuclear accumulation of the master regulator of the autophagy gene program, transcription factor EB. Lastly, we show that pharmacological AMPK stimulation normalizes the expression of myogenic regulatory factors and amends activated muscle stem cell content in mdx muscle. Our results indicate that AMPK activation via MK enhances disease‐mitigating mechanisms in dystrophic muscle and prefaces further investigation on the chronic effects of novel small molecule AMPK agonists. Abstract : A single, oral dose of the novel AMP‐activated protein kinase (AMPK) agonist MK‐8722 stimulates AMPK activity and signaling in skeletal and cardiac muscles of dystrophic mdx mice. This induces downstream mechanisms that drive the slow, oxidative muscle program (SOMP) including enhanced utrophin levels, augment autophagy signaling, and normalize muscle stem cell (MuSC) biology. Altogether, acute MK‐8722 exposure endows a disease‐resistant gene expression program in dystrophic muscle, which provides further evidence for the therapeutic potential of AMPK in Duchenne muscular dystrophy.